Trapped bodies, moving minds: Uncertainty and migration among marginalised urban youth in Ethiopia. (30th June 2021) - Johnson, Vicky; Getu, Melese; Getachew, Milki; Ahmed, Amid; West, Andy
Abstract: This paper from YOUR World Research highlights and explores the role of positive uncertainty in lives, strategies and transitions towards adulthood of marginalised children and youth in two urban locations in Ethiopia. Young men and women embraced notions of positive uncertainty, making journeys to street situations and internationally in search of more hopeful futures. While youth navigate uncertainty positively in the short term, the research suggests this is temporal and their agency relational and embedded. They seek support from peers but still want to belong and be accepted by their families and communities.